The Influence of Sheet Metal Forming on The Axial Crushing Analysis of Top–Hat Columns - Sigit P Santosa; Le Hoai Tam; Leonardo Gunawan; Annisa Jusuf (Mesin, 2016)
Reducing the rate of casualty in the crash events is always on the top priority of car manufacturers and customers. It is therefore necessary to make accurate predictions of car structural behavior during the crash events. To achieve this goal, the axial crushing behavior of the thin-walled top hat column needs to be understood thoroughly so that the crashworthiness performance of the column can be predicted accurately. The effect of sheet metal forming should be considered since many car crashworthiness components are fabricated by sheet metal forming. This paper presents a numerical study to investigate sheet metal forming effects such as: thickness distribution, residual stress and plastic strain change to the crushing force characteristics of the top-hat columns. First, the design of the top-hat column was generated by using deep drawing forming process simulation. Then, the forming parameters (geometry, residual stress, plastic strain, thickness distribution) were transferred to the non-linear finite element dynamic analysis model. The axial crushing simulations for the top-hat column with forming parameters were then performed and analyzed. The results showed that the sheet metal forming has a considerable effect on the crush behavior and performance of the thin-walled top-hat columns.